Polybutadiene, preparation method thereof and vulcanized rubber

By adopting specific antistatic agent addition methods and time points in polybutadiene rubber, combined with multi-step polymerization reaction method, the problem of poor distribution effect of conductive agent in tire materials is solved, and better antistatic performance and uniform distribution effect are achieved.

CN119841994APending Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311354543.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing conductive agents are mixed in tire materials, resulting in poor distribution effect and cannot fully exert antistatic properties.

Method used

Through specific addition methods and time points, the distribution of antistatic agents in polybutadiene rubber is improved, and a multi-step polymerization reaction method is adopted to ensure uniform distribution of antistatic agents, thereby improving antistatic properties.

Benefits of technology

The uniform distribution of antistatic agents in polybutadiene rubber is achieved, the antistatic properties of the final product are improved, and the reduction of butadiene conversion and poor distribution effect caused by the addition of antistatic agents are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004501758740000201
    Figure BDA0004501758740000201
Patent Text Reader

Abstract

The invention relates to the field of butadiene polymerization, and discloses polybutadiene for an anti-static tire, a preparation method of the polybutadiene and vulcanized rubber. The preparation method of polybutadiene comprises the following steps: 1) mixing a component N and a first component B, and aging to obtain a first mixed component; 2) mixing the component A, the second component B and the component D, and aging the mixture and the first component C to obtain a second mixed component; 3) performing polymerization reaction on butadiene, the first mixed component and the second component C; when the polymerization conversion rate is 65-80%, adding the component E, the component F and the second mixed component to carry out polymerization reaction; wherein the component N is nickel salt; the component B is an alkyl aluminum compound; a component C: a halogenated compound; a component D: conjugated diene; the component A is rare earth salt; component E and component F: a conductive material. According to the present invention, the polybutadiene with the good antistatic agent distribution effect, the preparation method thereof and the vulcanized rubber can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to the field of butadiene polymerization, and in particular to polybutadiene for antistatic tires, a preparation method thereof and vulcanized rubber. Background Art

[0002] Static electricity is a natural phenomenon that is generated by the friction between two different substances. In some rubber applications, static electricity is harmful. For example, static electricity generated when tires rub against the ground can easily damage electronic components, cause fires, and cause electric shock injuries to people if it is not removed in time. In order to eliminate the hazards of static electricity, the usual practice is to add a conductive agent during the tire rubber mixing process to achieve the purpose of removing static electricity.

[0003] Polybutadiene rubber has high elasticity, excellent wear resistance, good heat resistance, aging resistance, flexibility resistance, low heat generation, small hysteresis loss, etc., and the raw material resources are abundant and cheap, which is particularly suitable for tire manufacturing. Whether polybutadiene rubber and other materials such as antistatic agent materials can be mixed evenly during the post-processing mixing process is the key to the static removal effect. The post-processing process usually adopts the solid mixing method for mixing, and the mixing effect of this method is often unsatisfactory, which leads to the inability to give full play to the performance of the antistatic agent.

[0004] Since 1960, when American companies first realized the industrialized production of polybutadiene rubber using titanium catalysts and solution polymerization, with the development of the petrochemical industry, driven by the tire manufacturing industry, production has developed rapidly. By 1964, its production capacity jumped to the 1st place among the seven major general-purpose synthetic rubbers, second only to styrene-butadiene rubber. At present, many countries and regions around the world have industrial production facilities, but most of them only produce one brand, and homogeneous competition is serious. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem that the existing conductive agent is added to the tire rubber by mixing, which leads to poor distribution effect, and thus provide a polybutadiene with good antistatic agent distribution effect and a preparation method and vulcanized rubber.

[0006] Specifically, the method of the present invention can improve the distribution of the antistatic agent in the polybutadiene rubber, thereby improving the antistatic performance of the final product. Through a specific addition method and a specific addition time point, the decrease in butadiene conversion rate and the deterioration of the distribution effect caused by the additional addition of the antistatic agent can be avoided.

[0007] In order to achieve the above object, the present invention provides a method for preparing polybutadiene, wherein the method comprises:

[0008] 1) performing a first mixing of component N and a first component B and then performing a first aging to obtain a first mixed component;

[0009] 2) after performing a second mixing of component A, the second component B, and component D, performing a second aging of the second mixed product and the first component C to obtain a second mixed component;

[0010] 3) subjecting butadiene, the first mixed component and the second component C to a first polymerization reaction; when the polymerization conversion rate is 65-80%, adding the component E, the component F and the second mixed component to a second polymerization reaction;

[0011] Among them, component N is nickel salt; component B is alkyl aluminum compound; component C is halogenated compound; component D is conjugated diene; component A is rare earth salt; component E is the first conductive material; and component F is the second conductive material.

[0012] Preferably, in step 1), the molar ratio of the component N to the first component B is 1:2-12.

[0013] Preferably, based on 1 mmol of component N contained in the first mixed component, in step 2), the amount of component A is 0.05-12 mmol, the amount of the second component B is 2-15 mmol, the amount of component D is 10-50 mmol, and the amount of the first component C is 0.1-5 mmol.

[0014] Preferably, in step 2), the molar ratio of the component A, the second component B, the component D and the first component C is 1:10-25:5-100:2-4.

[0015] Preferably, based on 1 mmol of component N contained in the first mixed component, in step 3), the amount of the second component C used is 10-20 mmol.

[0016] Preferably, in step 3), the molar ratio of the butadiene, the first mixed component calculated as component N, the second component C and the second mixed component calculated as component A is 1:2×10 -5 -1.5×10 -4 : 5×10 -4 -3×10 -3 : 5×10 -5 -2.5×10 -4 .

[0017] Preferably, relative to 100 parts by mass of the butadiene, the amount of the first conductive material is 2-10 parts by mass, and the amount of the second conductive material is in the range of 5-40 parts by mass.

[0018] Preferably, the alkyl aluminum compound is selected from at least one of trialkyl aluminum and dialkyl aluminum hydride.

[0019] Preferably, the trialkylaluminum is represented by the formula Al(R)3, and the dialkylaluminum hydride is represented by the formula AlH(R)2, and each R in the formula Al(R)3 and the formula AlH(R)2 is independently selected from a C1-C6 alkyl group.

[0020] Preferably, the alkyl aluminum compound is at least one of trimethyl aluminum, triethyl aluminum, tri-n-propyl aluminum, tri-n-butyl aluminum, tri-n-pentylaluminum, tri-n-hexylaluminum, triisobutylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride and diisobutylaluminum hydride.

[0021] Preferably, the halogenated compound is selected from at least one of halogenated boron, halogenated hydrogen, halogenated alkylaluminum, halogenated silane and sesquihalogenated alkylaluminum.

[0022] Preferably, the alkyl aluminum halide is of the formula Al(R 1 )2X, the halogenated silane is represented by the formula Si(R 1 ) 4-n X n Said sesquihaloalkylaluminum is represented by the formula Al2(R 1 )3X3 represents, wherein the formula Al(R 1 )2X, formula Si(R 1 ) 4-n X n and Al2(R 1 ) Each R in 3X3 1 Each X is independently selected from C1-C6 alkyl, benzyl and allyl, each X is independently selected from halogen, and n is an integer of 1-4.

[0023] Preferably, the halogenated compound is at least one of diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, sesquiisobutylaluminum chloride, monochlorosilane, dichlorosilane, trichlorosilane tetrachlorosilane, hydrogen fluoride and boron trifluoride ether complex.

[0024] Preferably, the conjugated diene is at least one selected from 1,3-butadiene, isoprene, piperylene and 2,4-hexadiene.

[0025] Preferably, the nickel salt is at least one of nickel naphthenate, nickel octoate and nickel benzoate.

[0026] Preferably, the rare earth salt is at least one of a neodymium salt, a cerium salt and a praseodymium salt.

[0027] Preferably, the first conductive material is one or more of single-arm carbon nanotubes, multi-arm carbon nanotubes, silver fibers and copper fibers.

[0028] Preferably, the second conductive material is one or more of carbon black, graphite and aluminum powder.

[0029] Preferably, the first mixing conditions include: temperature of 10-40° C., and time of 10-200 min.

[0030] Preferably, the first aging conditions include: temperature of 10-40°C and time of 10-200 min.

[0031] Preferably, the second mixing conditions include: temperature of 10-40° C., and time of 10-200 min.

[0032] Preferably, the second aging conditions include: temperature of 40-80°C and time of 30-300 min.

[0033] Preferably, the temperature of the first polymerization reaction is 50-90°C.

[0034] Preferably, the temperature of the second polymerization reaction is 50-90°C.

[0035] Preferably, the total reaction time of the first polymerization reaction and the second polymerization reaction is 1-36 h, preferably 6-7 h.

[0036] Preferably, step 1) to step 3) are each independently carried out in an inert atmosphere.

[0037] Preferably, the inert atmosphere is provided by at least one of nitrogen, helium and argon.

[0038] Preferably, the first mixed component and the second mixed component each independently contain a solvent, and / or the raw materials for the first polymerization reaction contain a solvent.

[0039] Preferably, the solvent is C5-C 10 Alkanes, C5-C 10 Cycloalkanes and C6-C 12 At least one of aromatic hydrocarbons; more preferably, the solvent is at least one of pentane, cyclopentane, hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, benzene, toluene, xylene and cumene.

[0040] According to a second aspect of the present invention, provided is polybutadiene prepared by the method for preparing polybutadiene according to the first aspect of the present invention.

[0041] According to a third aspect of the present invention, there is provided a vulcanized rubber obtained by vulcanizing the polybutadiene obtained by the method for preparing polybutadiene according to the first aspect of the present invention.

[0042] The method provided by the present invention is conducive to improving the distribution of the antistatic agent in the polybutadiene rubber, thereby improving the antistatic performance of the final product. Through a specific adding method and a specific adding time point, the decrease in butadiene conversion rate and the deterioration of the distribution effect caused by the additional addition of the antistatic agent can be avoided.

[0043] Compared with the conventional mixing method, the method provided by the present invention has the advantage of more uniform distribution. Under the same antistatic effect, the antistatic dosage used in the method is less.

[0044] In addition, the antistatic polybutadiene rubber obtained by the method of the present invention can enrich the product grades of the nickel-based butadiene device without changing the original nickel-based device, and bring benefits to the enterprise without increasing the investment risk of the enterprise. DETAILED DESCRIPTION

[0045] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0046] A first aspect of the present invention provides a method for preparing polybutadiene, wherein the method comprises:

[0047] 1) performing a first mixing of component N and a first component B and then performing a first aging to obtain a first mixed component;

[0048] 2) after performing a second mixing of component A, the second component B, and component D, performing a second aging of the second mixed product and the first component C to obtain a second mixed component;

[0049] 3) subjecting butadiene, the first mixed component and the second component C to a first polymerization reaction; when the polymerization conversion rate is 65-80%, adding the component E, the component F and the second mixed component to a second polymerization reaction;

[0050] Among them, component N is nickel salt; component B is alkyl aluminum compound; component C is halogenated compound; component D is conjugated diene; component A is rare earth salt; component E is the first conductive material; and component F is the second conductive material.

[0051] In the present invention, the first component B and the second component B may be the same or different. Similarly, the first component C and the second component C may be the same or different.

[0052] The present invention is described below in steps, but it should be pointed out that the order of step 1) and step 2) of the present invention is not limited, and step 1) may be performed first and then step 2), or step 2) may be performed first and then step 1), or step 1) and step 2) may be performed simultaneously.

[0053] Step 1): Component N and the first component B are first mixed and then aged to obtain a first mixed component.

[0054] According to the present invention, in order to obtain polybutadiene rubber with excellent antistatic properties, preferably, in step 1), the molar ratio of the component N to the first component B is 1:2-12, more preferably 1:5-7.

[0055] Specific examples of the molar ratio of the component N and the first component B include: 1:2, 1:2, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, etc., and the range formed by any two of them.

[0056] According to the present invention, in order to obtain polybutadiene rubber with excellent antistatic properties, preferably, the first mixing conditions include: temperature of 10-40°C, time of 10-200 min; more preferably, the first mixing conditions include: temperature of 10-40°C, time of 20-60 min.

[0057] According to the present invention, in order to obtain polybutadiene rubber with excellent antistatic properties, preferably, the first aging conditions include: temperature of 10-40°C, time of 10-200 min; more preferably, the first aging conditions include: temperature of 15-35°C, time of 15-50 min.

[0058] According to the present invention, the component N is a nickel salt. The nickel salt may be various nickel salts commonly used in the art for butadiene polymerization. Preferably, the nickel salt is at least one of nickel naphthenate, nickel octanoate and nickel benzoate.

[0059] The nickel salt can be obtained by conventional methods in the art, for example, it can be a commercial product, or it can be prepared by conventional methods in the art, and the present invention has no particular limitation on this.

[0060] Step 2): After the component A, the second component B and the component D are mixed for the second time, the product after the second mixing is mixed with the first The first component C is subjected to a second aging to obtain a second mixed component.

[0061] According to the present invention, in order to obtain a polybutadiene rubber that is easy to process and has excellent wear resistance, based on the component N1mmol contained in the first mixed component, in step 2), the amount of component A is 0.05-1.2mmol, the amount of the second component B is 2-15mmol, the amount of component D is 10-50mmol, and the amount of the first component C is 0.1-5mmol; preferably, based on the component N1mmol contained in the first mixed component, in step 2), the amount of component A is 0.3-0.6mmol, the amount of the second component B is 5-9mmol, the amount of component D is 16-30mmol, and the amount of the first component C is 1-2mmol.

[0062] Taking the component N1mmol contained in the first mixed component as the reference, in step 2), specific examples of the amount of component A used include: 0.05mmol, 0.1mmol, 0.2mmol, 0.3mmol, 0.4mmol, 0.5mmol, 0.6mmol, 0.7mmol, 0.8mmol, 0.9mmol, 1mmol, 1.1mmol, 1.2mmol, etc., and the range formed by any two of them.

[0063] Taking the component N1mmol contained in the first mixed component as the reference, in step 2), specific examples of the amount of the component B used include: 2mmol, 3mmol, 4mmol, 5mmol, 6mmol, 7mmol, 8mmol, 9mmol, 10mmol, 11mmol, 12mmol, 13mmol, 14mmol, 15mmol, etc., and the range formed by any two of them.

[0064] Taking the component N1mmol contained in the first mixed component as the benchmark, in step 2), specific examples of the amount of the component C used include: 0.1mmol, 0.2mmol, 0.3mmol, 0.4mmol, 0.5mmol, 0.6mmol, 0.7mmol, 0.8mmol, 0.9mmol, 1mmol, 1.1mmol, 1.2mmol, 1.3mmol, 1.4mmol, 1.5mmol, 1.6mmol, 1.7mmol, 1.8mmol, 1.9mmol, 2mmol, 2.2mmol, 2.4mmol, 2.6mmol, 2.8mmol, 3mmol, 3.2mmol, 3.4mmol, 3.6mmol, 3.8mmol, 4mmol, 4.2mmol, 4.4mmol, 4.6mmol, 4.8mmol, 5mmol, etc., and the range formed by any two of them.

[0065] Taking the component N1mmol contained in the first mixed component as the benchmark, in step 2), specific examples of the amount of the component D used include: 10mmol, 11mmol, 12mmol, 13mmol, 14mmol, 15mmol, 16mmol, 17mmol, 18mmol, 19mmol, 20mmol, 21mmol, 22mmol, 23mmol, 24mmol, 25mmol, 26mmol, 27mmol, 28mmol, 29mmol, 30mmol, 31mmol, 32mmol, 33mmol, 34mmol, 35mmol, 36mmol, 37mmol, 38mmol, 39mmol, 40mmol, 41mmol, 42mmol, 43mmol, 44mmol, 45mmol, 46mmol, 47mmol, 48mmol, 49mmol, 50mmol, etc., and the range formed by any two of them.

[0066] Furthermore, in order to further improve the wear resistance of the obtained polybutadiene rubber, preferably, in step 2), the molar ratio of the component A, the second component B, the component D and the first component C is 1:10-25:5-100:2-4; more preferably, in step 2), the molar ratio of the component A, the second component B, the component D and the first component C is 1:12-20:2.5-3.5:10-80.

[0067] According to the present invention, in order to obtain polybutadiene rubber with excellent antistatic properties, preferably, the second mixing conditions include: temperature of 10-40°C, time of 10-200 min; more preferably, the second mixing conditions include: temperature of 10-40°C, time of 20-60 min.

[0068] According to the present invention, in order to obtain a polybutadiene rubber that is easy to process and has excellent wear resistance, preferably, the second aging conditions include: a temperature of 40-80°C and a time of 30-300 min; more preferably, the second aging conditions include: a temperature of 50-70°C and a time of 60-120 min.

[0069] According to the present invention, the component A is a rare earth salt. The rare earth salt may be various rare earth salts commonly used in the art for butadiene polymerization. Preferably, the rare earth salt is at least one of a neodymium salt, a cerium salt and a praseodymium salt. Examples of the rare earth salt include at least one of neodymium octanoate, neodymium cyclohexaneate and neodymium phosphonate.

[0070] The rare earth salt can be obtained by conventional methods in the art, for example, it can be a commercial product, or it can be prepared by conventional methods in the art, and the present invention has no particular limitation on this.

[0071] According to the present invention, the component B is an alkyl aluminum compound. The alkyl aluminum compound can be various alkyl aluminum compounds commonly used in the art for butadiene polymerization. In order to further improve the wear resistance of the obtained polybutadiene rubber, preferably, the alkyl aluminum compound is selected from at least one of trialkyl aluminum and dialkyl aluminum hydride; more preferably, the trialkyl aluminum is represented by the formula Al(R)3, and the dialkyl aluminum hydride is represented by the formula AlH(R)2, and each R in the formula Al(R)3 and the formula AlH(R)2 is independently selected from the alkyl group of C1-C6; further preferably, the alkyl aluminum compound is at least one of trimethyl aluminum, triethyl aluminum, tri-n-propyl aluminum, tri-n-butyl aluminum, tri-n-pentyl aluminum, tri-n-hexyl aluminum, tri-isobutyl aluminum, diethyl aluminum hydride, di-n-propyl aluminum hydride, di-n-butyl aluminum hydride and di-isobutyl aluminum hydride.

[0072] According to the present invention, the component C is a halogenated compound. The halogenated compound may be various halogenated compounds commonly used in the art for butadiene polymerization. In order to further improve the wear resistance of the obtained polybutadiene rubber, preferably, the halogenated compound is selected from at least one of halogenated boron, halogenated hydrogen, halogenated alkyl aluminum, halogenated silane and sesquihalogenated alkyl aluminum; more preferably, the halogenated alkyl aluminum is represented by the formula Al(R 1 )2X, halosilane is represented by the formula Si(R 1 ) 4-n X n Said, sesquihaloalkylaluminum is represented by the formula Al2(R 1)3X3 represents, wherein the formula Al(R 1 )2X, formula Si(R 1 ) 4-n X n and Al2(R 1 ) Each R in 3X3 1 Each is independently selected from C1-C6 alkyl, benzyl and allyl, each X is independently selected from halogen, and n is an integer of 1-4; further preferably, the halogenated compound is at least one of diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, sesquiisobutylaluminum chloride, monochlorosilane, dichlorosilane, trichlorosilane tetrachloride, hydrogen fluoride and boron trifluoride ether complex.

[0073] According to the present invention, the component D is a conjugated diene. The active center of the catalyst can be stabilized by the component D being a conjugated diene. The conjugated diene refers to an olefin monomer having a conjugated double bond, and the conjugated diene may be the same as the polymerizable monomer or different from the polymerizable monomer. In order to further improve the catalytic activity of the composition, preferably, the conjugated diene is at least one of 1,3-butadiene, isoprene, piperylene and 2,4-hexadiene.

[0074] Step 3): subjecting butadiene, the first mixed component, and the second component C to a first polymerization reaction; at a polymerization conversion rate of When the content of the component is 65-90%, component E, component F and the second mixed component are added to carry out a second polymerization reaction.

[0075] According to the present invention, in order to further improve the antistatic properties of the obtained polybutadiene rubber, preferably, based on the component N1mmol contained in the first mixed component, in step 3), the amount of the second component C is 10-20mmol; more preferably, based on the component N1mmol contained in the first mixed component, in step 3), the amount of the second component C is 14-17mmol.

[0076] Taking the component N1mmol contained in the first mixed component as a reference, in step 3), specific examples of the amount of the second component C used include: 10mmol, 11mmol, 12mmol, 13mmol, 14mmol, 15mmol, 16mmol, 17mmol, 18mmol, 19mmol, 20mmol, etc., and the range formed by any two of them.

[0077] According to the present invention, in order to further improve the antistatic property of the obtained polybutadiene rubber, preferably, in step 3), the molar ratio of the butadiene, the first mixed component calculated as component N, the second component C and the second mixed component calculated as component A is 1:2×10 -5 -15×10 -5 : 5×10 -4 -3×10-3 : 5×10 -5 -2.5×10 -4 More preferably, in step 3), the molar ratio of the second butadiene, the first mixed component calculated as component N, the second component C and the second mixed component calculated as component A is 1:6×10 -5 -1×10 -4 :1×10 -3 -2×10 -3 :1.2×10 -4 -1.8×10 -4 .

[0078] According to the present invention, in order to further improve the antistatic properties of the obtained polybutadiene rubber, preferably, when the polymerization conversion rate is 70-80%, component E, component F and the second mixed component are added to carry out a second polymerization reaction; more preferably, when the polymerization conversion rate is 75-80%, component E, component F and the second mixed component are added to carry out a second polymerization reaction.

[0079] Specific examples of the polymerization conversion rate include 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, etc., and ranges consisting of any two of them.

[0080] According to the present invention, in order to further improve the antistatic property of the obtained polybutadiene rubber, preferably, relative to 100 parts by mass of the butadiene, the amount of the first conductive material is 2-10 parts by mass, and the amount of the second conductive material is 5-40 parts by mass; more preferably, relative to 100 parts by mass of the butadiene, the amount of the first conductive material is 2.5-9.5 parts by mass, and the amount of the second conductive material is 8-35 parts by mass; more preferably, relative to 100 parts by mass of the butadiene, the amount of the first conductive material is 2.5-6 parts by mass, and the amount of the second conductive material is 10-30 parts by mass.

[0081] In the present invention, the first conductive material and the second conductive material are used as antistatic agents. The method of the present invention can improve the distribution of the antistatic agent in the polybutadiene rubber, thereby improving the antistatic performance of the final product, and can avoid the decrease in butadiene conversion rate and the deterioration of the distribution effect caused by the additional addition of the antistatic agent through a specific addition method and a specific addition time point.

[0082] Therefore, the present invention has no particular limitation on the conductive material, and it can be any conductive material that generally has an antistatic effect in the art.

[0083] Preferably, the first conductive material is one or more of single-arm carbon nanotubes, multi-arm carbon nanotubes, silver fibers and copper fibers.

[0084] In addition, preferably, the second conductive material is one or more of carbon black, graphite and aluminum powder.

[0085] In a preferred embodiment of the present invention, the first conductive material is multi-arm carbon nanotubes, and the second conductive material is carbon black.

[0086] In another preferred embodiment of the present invention, the first conductive material is multi-arm carbon nanotubes, and the second conductive material is aluminum powder.

[0087] In another preferred embodiment of the present invention, the first conductive material is silver fiber, and the second conductive material is graphite.

[0088] In another preferred embodiment of the present invention, the first conductive material is copper fiber, and the second conductive material is carbon black.

[0089] In the present invention, the first conductive material and the second conductive material are used as antistatic agents. Preferably, the first conductive material is a single-arm carbon nanotube. In addition, preferably, the second conductive material is carbon black.

[0090] In a preferred embodiment of the present invention, the first conductive material is a single-arm carbon nanotube, and the second conductive material is carbon black.

[0091] According to the present invention, in order to further improve the antistatic property of the obtained polybutadiene rubber, preferably, the first polymerization reaction and the second polymerization reaction each independently satisfy at least the following conditions: the temperature is 50-90°C, preferably 50-65°C.

[0092] In the present invention, preferably, the total reaction time of the first polymerization reaction and the second polymerization reaction is 1-36 h, more preferably 6-7 h.

[0093] In addition, in order to prevent oxygen from destroying the active center of the catalyst, preferably, step 1) to step 3) are each independently carried out in an inert atmosphere; more preferably, the inert atmosphere is provided by at least one of nitrogen, helium and argon.

[0094] At the same time, in order to smoothly construct the active center of the catalyst and have higher catalytic activity, preferably, the first mixed component and the second mixed component each independently contain a solvent, and / or the raw material of the first polymerization reaction contains a solvent; more preferably, the solvent is C5-C 10 Alkanes, C5-C 10 Cycloalkanes and C6-C 12further preferably, the solvent is at least one of pentane, cyclopentane, hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, benzene, toluene, xylene and cumene.

[0095] In the above embodiment, in order to further improve the activity of the catalyst, preferably, the concentration of component N in the first mixed component and the second mixed component is 0.01-1 mmol / mL, preferably 0.05-0.2 mmol / mL, and more preferably 0.08-0.12 mmol / mL.

[0096] In the above embodiment, the solvent may be added in the form of a pure substance or in the form of a solution with other reactants.

[0097] On this basis, the component N in the catalyst composition can be provided in the form of a pure substance or in the form of a solution. When the component N is provided in the form of a solution, the concentration of the solution of the component N can be, for example, 0.01-0.5 mol / L. The solvent can be selected from the first organic solvent used in the homogeneous solution described above.

[0098] Similarly, component B in the catalyst composition can be provided in the form of a pure substance or in the form of a solution. When component B is provided in the form of a solution, the concentration of the solution of component B can be, for example, 0.01-5 mol / L. The solvent can be selected from the first organic solvent used in the homogeneous solution described above.

[0099] Similarly, component C in the catalyst composition can be provided in the form of a pure substance or in the form of a solution. When component C is provided in the form of a solution, the concentration of the solution of component C can be, for example, 0.0001-5 mol / L. The solvent can be selected from the first organic solvent used in the homogeneous solution described above.

[0100] Similarly, component D in the catalyst composition can be provided in the form of a pure substance or in the form of a solution. When component D is provided in the form of a solution, the concentration of the solution of component D can be, for example, 0.01-5 mol / L. The solvent can be selected from the first organic solvent used in the homogeneous solution described above.

[0101] Similarly, component A in the catalyst composition can be provided in the form of a pure substance or in the form of a solution. When component A is provided in the form of a solution, the concentration of the solution of component A can be, for example, 0.01-0.5 mol / L. The solvent can be selected from the first organic solvent used in the homogeneous solution described above.

[0102] In addition, butadiene can be provided in the form of a pure substance or in the form of a solution. When butadiene is provided in the form of a solution, the weight ratio of butadiene to the solvent is 100:300-1000. The solvent can be C5-C 10 Alkanes, C5-C 10 Cycloalkanes and C6-C 12 more preferably, the solvent is at least one of pentane, cyclopentane, hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, benzene, toluene, xylene and cumene.

[0103] According to a second aspect of the present invention, there is provided the polybutadiene prepared according to the first aspect of the present invention.

[0104] According to a third aspect of the present invention, there is provided a vulcanized rubber obtained by vulcanizing the polybutadiene obtained by the method according to the first aspect of the present invention.

[0105] There are no particular limitations on the formula and method for vulcanization, and the formula and method may be conventional in the art.

[0106] In a specific embodiment of the present invention, the vulcanized formula is: 100 parts by mass of polybutadiene rubber; 5 parts by mass of zinc oxide; 2 parts by mass of stearic acid; 1 part by mass of antioxidant 1520; 1 part by mass of antioxidant 1076; 1.4 parts by mass of sulfur, and 1 part by mass of accelerator. The accelerator may be N-cyclohexyl-2-benzothiazole sulfenamide (CBS).

[0107] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.

[0108] In the following examples and comparative examples, unless otherwise specified, all raw materials used were commercially available.

[0109] The polymerization monomer conversion rate was calculated as follows.

[0110] Monomer conversion rate (conv) = mass of polymerized product / total mass of monomers input × 100%

[0111] Example 1

[0112] Under nitrogen protection, 100 mL of hexane, 2.8 mmol of neodymium octanoate, and then 51.2 mL of a 1 mol / L hexane solution of diisobutylaluminum hydride and 160 mmol of butadiene were added, stirred and mixed at 30°C for 30 min, then the temperature was raised to 60°C, and 8.4 mL of a 1 mol / L hexane solution of diethylaluminum chloride was added, and the mixture was aged for 2 h to obtain a catalyst in a homogeneous solution state, i.e., homogeneous rare earth catalyst C1.

[0113] Under nitrogen protection, 10 mL of hexane, 0.33 mmol of nickel cyclohexane, and 1.96 mmol of triisobutylaluminum were mixed at 30°C for 10 min, and then aged at 30°C for 30 min. The above solution was put into a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component calculated as nickel cyclohexane was 1:8.8×10 -5 ), and then 0.13 mmol of boron trifluoride etherate complex was added (the molar ratio of butadiene to boron trifluoride etherate complex was 1:1.32×10 -3 ), mixed well, and polymerized at a polymerization temperature of 55°C. When the conversion rate of the reaction reached 80%, 5 g of multi-arm carbon nanotubes, 40 g of carbon black, and 6.6 mL of catalyst C1 (the molar ratio of butadiene to the catalyst calculated as neodymium octanoate was 1:1.5×10 -4 ), the reaction was continued at a polymerization temperature of 60°C for 5 hours, butadiene was completely converted, and polybutadiene was obtained after condensation and drying. The test results of the obtained polymer after mixing and vulcanization according to the formula are shown in Table 1.

[0114] Example 2

[0115] The homogeneous rare earth catalyst C1 was obtained according to the method of Example 1.

[0116] Under nitrogen protection, 10 mL of hexane, 0.33 mmol of nickel cyclohexane, and 1.96 mmol of triisobutylaluminum were mixed at 30°C for 10 min, and then aged at 30°C for 30 min. The above solution was then put into a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component calculated as nickel cyclohexane was 1:8.8×10 -5 ), and then 0.13 mmol of boron trifluoride etherate complex was added (the molar ratio of butadiene to boron trifluoride etherate complex was 1:1.32×10 -3 ), mixed, and polymerized at a polymerization temperature of 50°C. When the conversion rate of the reaction reached 80%, 10.9 g of copper fiber, 30 g of carbon black, and 6.6 mL of catalyst C1 (the molar ratio of butadiene to the catalyst calculated as neodymium octanoate was 1:1.5×10 -4 ), the reaction was continued at a polymerization temperature of 70°C for 5 hours, and polybutadiene was obtained after condensation and drying. The test results of the obtained polymer after mixing and vulcanization according to the formula are shown in Table 1.

[0117] Example 3

[0118] The homogeneous rare earth catalyst C1 was obtained according to the method of Example 1.

[0119] Under nitrogen protection, 10 mL of hexane, 0.33 mmol of nickel cyclohexane, and 1.96 mmol of triisobutylaluminum were mixed at 30°C for 10 min, and then aged at 30°C for 30 min. The above solution was then put into a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component calculated as nickel cyclohexane was 1:8.8×10 -5 ), and then 0.13 mmol of boron trifluoride etherate complex was added (the molar ratio of butadiene to boron trifluoride etherate complex was 1:1.32×10 -3 ), mixed well, and polymerized at a polymerization temperature of 60°C. When the conversion rate of the reaction reached 80%, 7.3 g of silver fiber, 60 g of graphite, and 6.6 mL of catalyst C1 (the molar ratio of butadiene to the catalyst calculated as neodymium octanoate was 1:1.5×10 -4 ), the reaction was continued at a polymerization temperature of 80°C for 5 hours, and polybutadiene was obtained after condensation and drying. The test results of the obtained polymer after mixing and vulcanization according to the formula are shown in Table 1.

[0120] Example 4

[0121] The homogeneous rare earth catalyst C1 was obtained according to the method of Example 1.

[0122] Under nitrogen protection, 10 mL of hexane, 0.33 mmol of nickel cyclohexane, and 1.96 mmol of triisobutylaluminum were mixed at 30°C for 10 min, and then aged at 30°C for 30 min. The above solution was then put into a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component calculated as nickel cyclohexane was 1:8.8×10 -5 ), and then 0.13 mmol of boron trifluoride etherate complex was added (the molar ratio of butadiene to boron trifluoride etherate complex was 1:1.32×10 -3 ), mixed well, and polymerized at a polymerization temperature of 50°C. When the conversion rate of the reaction reached 65%, 18.2 g of multi-arm carbon nanotubes, 40 g of aluminum powder, and 6.1 mL of catalyst C1 (the molar ratio of butadiene to the catalyst calculated as neodymium octanoate was 1:1.5×10 -4 ), the reaction was continued at a polymerization temperature of 90°C for 5 hours, and polybutadiene was obtained after condensation and drying. The test results of the obtained polymer after mixing and vulcanization according to the formula are shown in Table 1.

[0123] Example 5

[0124] The homogeneous rare earth catalyst C1 was obtained according to the method of Example 1.

[0125] Under nitrogen protection, 10 mL of hexane, 0.33 mmol of nickel cyclohexane, and 1.96 mmol of triisobutylaluminum were mixed at 30°C for 10 min, and then aged at 30°C for 30 min. The above solution was then put into a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component calculated as nickel cyclohexane was 1:8.8×10 -5 ), and then 0.13 mmol of boron trifluoride etherate complex was added (the molar ratio of butadiene to boron trifluoride etherate complex was 1:1.32×10 -3 ), mixed well, and polymerized at a polymerization temperature of 60°C. When the conversion rate of the reaction reached 78%, 10.9 g of multi-arm carbon nanotubes, 20 g of carbon black, and 7.6 mL of catalyst C1 (the molar ratio of butadiene to the catalyst calculated as neodymium octanoate was 1:1.5×10 -4 ), the reaction was continued at a polymerization temperature of 60°C for 5 hours, and polybutadiene was obtained after condensation and drying. The test results of the obtained polymer after mixing and vulcanization according to the formula are shown in Table 1.

[0126] Example 6

[0127] Under nitrogen protection, 100 mL of hexane, 0.28 mmol of neodymium octanoate, and then 33.6 mL of a 1 mol / L hexane solution of diisobutylaluminum hydride and 224 mmol of butadiene were added, stirred and mixed at 30°C for 30 min, then the temperature was raised to 60°C, and 7 mL of a 1 mol / L hexane solution of diethylaluminum chloride was added, and the mixture was aged for 2 h to obtain a catalyst in a homogeneous solution state, i.e., homogeneous rare earth catalyst C2.

[0128] Under nitrogen protection, 10 mL of hexane, 0.37 mmol of nickel cyclohexane, and 2.59 mmol of triisobutylaluminum were mixed at 30°C for 10 min, and then aged at 30°C for 30 min. The above solution was put into a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component calculated as nickel cyclohexane was 1:6×10 -5 ), and then 0.13 mmol of boron trifluoride ether complex was added (the molar ratio of butadiene to boron trifluoride ether complex was 1:1.0×10 -3 ), mixed well, and polymerized at a polymerization temperature of 50°C. When the conversion rate of the reaction reached 80%, 5 g of multi-arm carbon nanotubes, 40 g of carbon black, and 6.6 mL of catalyst C2 (the molar ratio of butadiene to the catalyst calculated as neodymium octanoate was 1:1.2×10 -4), the reaction was continued at a polymerization temperature of 60°C for 5 hours, butadiene was completely converted, and polybutadiene was obtained after condensation and drying. The test results of the obtained polymer after mixing and vulcanization according to the formula are shown in Table 1.

[0129] Example 7

[0130] Under nitrogen protection, 100 mL of hexane, 2.8 mmol of neodymium octanoate, and then 56 mL of a 1 mol / L hexane solution of diisobutylaluminum hydride and 28 mmol of butadiene were added, stirred and mixed at 30°C for 30 min, then the temperature was raised to 60°C, and 9.8 mL of a 1 mol / L hexane solution of diethylaluminum chloride was added, and the mixture was aged for 2 h to obtain a catalyst in a homogeneous solution state, i.e., homogeneous rare earth catalyst C2.

[0131] Under nitrogen protection, 10 mL of hexane, 0.22 mmol of nickel cyclohexane, and 1.1 mmol of triisobutylaluminum were mixed at 30°C for 10 min, and then aged at 30°C for 30 min. The above solution was put into a reactor containing 200 g of butadiene (monomer) and 900 g of hexane (the molar ratio of butadiene to the first mixed component calculated as nickel cyclohexane was 1:1×10 -4 ), and then 0.13 mmol of boron trifluoride etherate complex was added (the molar ratio of butadiene to boron trifluoride etherate complex was 1:1.4×10 -3 ), mixed well, and polymerized at a polymerization temperature of 60°C. When the conversion rate of the reaction reached 80%, 5 g of multi-arm carbon nanotubes, 40 g of carbon black, and 6.6 mL of catalyst C2 (the molar ratio of butadiene to the catalyst calculated as neodymium octanoate was 1:1.8×10 -4 ), the reaction was continued at a polymerization temperature of 60°C for 5 hours, butadiene was completely converted, and polybutadiene was obtained after condensation and drying. The test results of the obtained polymer after mixing and vulcanization according to the formula are shown in Table 1.

[0132] Comparative Example 1

[0133] The polymerization method described in Example 1 is used, except that multi-arm carbon nanotubes and carbon black are added during mixing. The test results after vulcanization are shown in Table 1.

[0134] Comparative Example 2

[0135] The polymerization method according to Example 1 is different in that multi-arm carbon nanotubes and carbon black are added during mixing, and the added amount of multi-arm carbon nanotubes is 9 g, and the added amount of carbon black is 80 g. The test results after vulcanization are shown in Table 1.

[0136] Comparative Example 3

[0137] The polymerization method described in Example 1 is used, except that multi-arm carbon nanotubes and carbon black are added when the conversion rate is 85%. The test results after vulcanization are shown in Table 1.

[0138] Comparative Example 4

[0139] The polymerization method is based on the one described in Example 1, except that when the conversion rate is 60%, multi-arm carbon nanotubes and carbon black are added, and the final butadiene conversion rate is 83%.

[0140] Test Example 1

[0141] The polybutadiene obtained in Examples 1-7 and Comparative Examples 1-4 was vulcanized according to the following formulation.

[0142] The vulcanization method is as follows: each sample is processed and analyzed according to GB / T 8660-2008, the mixing adopts a two-stage method, both are carried out in an internal mixer, and the vulcanization conditions are 145°C×35min.

[0143] Mixing and vulcanization formula: 100 parts of polybutadiene rubber; 5 parts of zinc oxide; 2 parts of stearic acid; 1 part of antioxidant 1520; 1 part of antioxidant 1076; 1.4 parts of sulfur, 1 part of accelerator. The accelerator is N-cyclohexyl-2-benzothiazole sulfenamide (CBS).

[0144] The following properties were tested on the vulcanized rubber.

[0145] Tensile strength, tear strength and elongation test: With reference to the test method specified in GB / T 528-1998 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, the tensile strength, tear strength and elongation of each embodiment and comparative example sample were tested.

[0146] Resistivity test: Referring to the test method in GBT1410-2006 Resistivity Test Standard, the resistivity test was performed on each embodiment and comparative example.

[0147] The results are shown in Table 1.

[0148] Table 1

[0149]

[0150] From the above results, it can be seen that the antistatic agent needs to be added when the conversion rate of the first stage reaction is within the range of 65-80% in order to achieve complete conversion of the final monomer and ensure the antistatic effect. In addition, under the same antistatic agent addition conditions, adding the antistatic agent during the polymerization process is better than adding the antistatic agent during the mixing process; and to achieve the same antistatic performance, the amount of antistatic agent added in the mixing method is more than that added in the polymerization, which shows that the dispersion effect of the antistatic agent added in the polymerization process is better than that of the mixing method.

[0151] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing polybutadiene, characterized in that: The method includes: 1) performing a first mixing of component N and a first component B and then performing a first aging to obtain a first mixed component; 2) after performing a second mixing of component A, the second component B, and component D, performing a second aging of the second mixed product and the first component C to obtain a second mixed component; 3) subjecting butadiene, the first mixed component and the second component C to a first polymerization reaction; when the polymerization conversion rate is 65-80%, adding the component E, the component F and the second mixed component to a second polymerization reaction; Among them, component N is nickel salt; component B is alkyl aluminum compound; component C is halogenated compound; component D is conjugated diene; component A is rare earth salt; component E is the first conductive material; and component F is the second conductive material.

2. The method according to claim 1, wherein: In step 1), the molar ratio of the component N to the first component B is 1:2-12.

3. The method according to claim 1, wherein: Based on 1 mmol of component N contained in the first mixed component, in step 2), the amount of component A is 0.05-12 mmol, the amount of the second component B is 2-15 mmol, the amount of component D is 10-50 mmol, and the amount of the first component C is 0.1-5 mmol; Preferably, in step 2), the molar ratio of the component A, the second component B, the component D and the first component C is 1:10-25:5-100:2-4.

4. The method according to any one of claims 1 to 3, wherein: Based on 1 mmol of component N contained in the first mixed component, in step 3), the amount of the second component C is 10-20 mmol; Preferably, in step 3), the molar ratio of the butadiene, the first mixed component calculated as component N, the second component C and the second mixed component calculated as component A is 1:2×10 -5 -1.5×10 -4 : 5×10 -4 -3×10 -3 : 5×10 -5 -2.5×10 -4 ; Preferably, relative to 100 parts by mass of the butadiene, the amount of the first conductive material is 2-10 parts by mass, and the amount of the second conductive material is 5-40 parts by mass.

5. The method according to any one of claims 1 to 3, wherein: The alkyl aluminum compound is selected from at least one of trialkyl aluminum and dialkyl aluminum hydride; Preferably, the trialkylaluminum is represented by the formula Al(R)3, and the dialkylaluminum hydride is represented by the formula AlH(R)2, and each R in the formula Al(R)3 and the formula AlH(R)2 is independently selected from a C1-C6 alkyl group; More preferably, the alkylaluminum compound is at least one of trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, tri-n-pentylaluminum, tri-n-hexylaluminum, triisobutylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride and diisobutylaluminum hydride.

6. The method according to any one of claims 1 to 3, wherein: The halogenated compound is selected from at least one of halogenated boron, halogenated hydrogen, halogenated alkylaluminum, halogenated silane and sesquihalogenated alkylaluminum; Preferably, the alkyl aluminum halide is of the formula Al(R 1 )2X, the halogenated silane is represented by the formula Si(R 1 ) 4-n X n Said sesquihaloalkylaluminum is represented by the formula Al2(R 1 )3X3 represents, wherein the formula Al(R 1 )2X, formula Si(R 1 ) 4-n X n and Al2(R 1 ) Each R in 3X3 1 Each is independently selected from C1-C6 alkyl, benzyl and allyl, each X is independently selected from halogen, and n is an integer of 1-4; Preferably, the halogenated compound is at least one of diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, sesquiisobutylaluminum chloride, monochlorosilane, dichlorosilane, trichlorosilane tetrachlorosilane, hydrogen fluoride and boron trifluoride ether complex.

7. The method according to any one of claims 1 to 3, wherein: The conjugated diene is selected from at least one of 1,3-butadiene, isoprene, piperylene and 2,4-hexadiene; Preferably, the nickel salt is at least one of nickel naphthenate, nickel octoate and nickel benzoate; Preferably, the rare earth salt is at least one of a neodymium salt, a cerium salt and a praseodymium salt; Preferably, the first conductive material is one or more of single-arm carbon nanotubes, multi-arm carbon nanotubes, silver fibers and copper fibers; Preferably, the second conductive material is one or more of carbon black, graphite and aluminum powder.

8. The method according to any one of claims 1 to 3, wherein: The first mixing conditions include: temperature of 10-40°C and time of 10-200 min; Preferably, the first aging conditions include: temperature of 10-40°C and time of 10-200 min; Preferably, the second mixing conditions include: temperature of 10-40°C and time of 10-200 min; Preferably, the second aging conditions include: temperature of 40-80°C and time of 30-300 min.

9. The method according to any one of claims 1 to 3, wherein: The temperature of the first polymerization reaction is 50-90°C; Preferably, the temperature of the second polymerization reaction is 50-90°C; Preferably, the total reaction time of the first polymerization reaction and the second polymerization reaction is 1-36 h, preferably 6-7 h.

10. The method according to any one of claims 1 to 3, wherein: Step 1) to step 3) are each independently carried out in an inert atmosphere; Preferably, the inert atmosphere is provided by at least one of nitrogen, helium and argon.

11. The method according to any one of claims 1 to 3, wherein: The first mixed component and the second mixed component each independently contain a solvent, and / or the raw material of the first polymerization reaction contains a solvent; Preferably, the solvent is C5-C 10 Alkanes, C5-C 10 Cycloalkanes and C6-C 12 At least one of the aromatic hydrocarbons; More preferably, the solvent is at least one of pentane, cyclopentane, hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, benzene, toluene, xylene and cumene.

12. Polybutadiene prepared by the method for preparing polybutadiene according to any one of claims 1 to 11.

13. A vulcanized rubber obtained by vulcanizing polybutadiene obtained by the method for preparing polybutadiene according to any one of claims 1 to 11.